Where Poverty Matters: Examining the Cross-national Relationship Between Economic Deprivation and Homicide. (3rd March 2017) - Rennó Santos, Mateus; Testa, Alexander; Weiss, Douglas B
Abstract: Recent research on the role of economic deprivation in explaining cross-national homicide rates is inconsistent. These inconsistencies may be attributed to the use of samples composed primarily of developed countries, and the implicit assumption that the impact of deprivation is constant throughout the homicide distribution. The current study challenges this assumption and suggests a dynamic relationship between deprivation and homicide. Using a broad sample of 148 countries this work applies quantile regression to examine whether inequality and poverty have consistent impacts across the entire homicide distribution. Results indicate that inequality and homicide have a universal positive relationship. In contrast, poverty is only related to homicide in countries with lower homicide rates. Findings are discussed within the context of strain theory.